Gender pay gap varies greatly by occupation - Katharina Wrohlich (DIW Economic Bulletin, 2017)
The German labor market is characterized by marked occupational segregation between women and men. The median earnings in female dominated occupations are lower than those in male dominated professions. This is one of the reasons for the gender pay gap. However, there are also large differences in earnings between men and women within occupations. These profession-specific gender pay gaps are smaller in professions with a high proportion of employees in the public sector. This finding indicates that more transparency with respect to earnings could reduce the gender pay gap in the private economy.
Keywords: J31; J16; 330; gender pay gap; occupational segregation